APPLICATION OF THE JOURNALISTIC CODE OF ETHICS ON THE PROTECTION OF SEXUAL VIOLENCE NEWS SOURCE AT “LIPUTAN6.COM” - Marcella Putri Cahyani; regina sofya; W Wahyunengsih (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2022)
This article is a research article related to the application of a journalistic code of ethics to sexual violence news sources at "Liputan6.com." The purpose of this study was to determine the quality of reporting on Liputan6.com and to determine the application of the Journalism Professional Code of Ethics on the online media news portal Liputan6.com. The method used in this study is a qualitative method, where this method emphasizes the application of writing online news on the Liputan6.com port. This study concludes that Liputan6.com has implemented a code of ethics for the journalistic profession and has displayed news of sexual violence correctly by the press council's professional code of ethics.